Living Hadith: The Art of Jathilan Suryo Budoyo as a Media for Da'wah: Roland Barthes' Semiotic Analysis - Arhanudri Davi Mawarni; Zainudin, Zainudin; Restendy, Mochammad Sinung (DAWUH : Islamic Communication Journal, 2026)
Art is an integral part of Indonesian society. Through art, various meanings or messages can be effectively conveyed. The role of art has a positive impact on the development of da'wah (Islamic propagation) in this country. One such art form is the Suryo Budoyo jathilan (jathilan dance). The purpose of this study is to examine the art form "Jathilan Suryo Budoyo" as a medium for da'wah from a Hadith perspective. This research method uses a descriptive qualitative approach with data collection techniques such as field observation and documentation. To analyze the data, the author employed semiotic analysis developed by Roland Barthes, namely: denotation, connotation, and myth. The results of this study indicate that the semiotic analysis of the Suryo Budoyo jathilan art form serves as a reminder to maintain a good relationship with Allah SWT and social life. Meaning is embedded in each component, including the pengrawit (singer), paraga (singer), and pawang (pawang), each of which has its own da'wah message